Physical Responses of Pinctada fucata to Salinity Stress - Yang, Jingru; Yang, Jinling; Chen, Mingqiang; Fu, Zhengyi; Sun, Jing; Yu, Gang; Wang, Aimin; Ma, Zhenhua; Gu, Zhifeng (Frontiers in Marine Science, 2022)
This study was conducted to understand the changes of physiological and biochemical indexes of black and red shell Pinctada fucata under acute high-salt and low-salt stress. In this study 35‰ salinity was used as the control, while 20‰ salinity was used as the low-salt treatment group, and 50‰ salinity was used as the high-salt treatment group. The osmotic pressure (OSM) and ion concentration in hemolymph, NAK activity and respiratory metabolism in gills, antioxidant and immune (non-) enzymes in hepatopancreas of P. fucata with two shell colors under salinity stress were compared and analyzed. The results showed that the OSM and inorganic ion (Na+, Ca2+ and Cl−) concentration in hemolymph of the black and red P. fucata increased significantly with the increase of salinity after 1.5 h and 3 h. At 3 h, the black P. fucata Na+-K+ -ATPase (NKA) activity decreased significantly with the increase of salinity, while the red P. fucata reached the highest value at high salinity. The succinate dehydrogenase (SDH) and lactate dehydrogenase (LDH) activities of red P. fucata showed U-shaped and inverted U-shaped distributions with the increase of salinity after 1.5 h, respectively. With the increase of salinity, the phenoloxidase (POX) activity of red and black P. fucata showed inverted U-shaped and U-shaped distribution, respectively. Results from the present study revealed that the sensitivity of P. fucata to salinity varied in shell color. Compared to black P. fucata, red P. fucata responds more quickly to sharp salinity changes, thereby reducing more likely damage. Compared with the high-salt environment, P. fucata was more adaptable to the changes of acute low-salt environment. Results from the present study provide the physical references for subsequent selective breeding of this species.